A correlation for predicting the viscosity of Nigerian crude oils (1990)
An empirical equation that could be used for predicting the viscosity of Nigerian crudes is presented in this paper. The correlation uses oil specific gravity as the main correlating parameter, and also incorporates the effects of reservoir pressure, temperature and oil formation volume factor. Data from well over 400 samples of Nigerian crudes were used for developing the correlation, with most samples however, from reservoirs at or above saturation pressure. The results show however that the correlation could have general applicability. The correlation when compared with some earlier works proved to be more accurate for Nigerian crudes. Graphical and Statistical error analyses undertaken suggest good performance and accuracy. The correlation should prove valid for estimating the viscosity of Nigerian crudes, as well as other crude types having properties that fall within the range of the data used in this work.